Gut Microbiota and its Impact on Chronic Diseases: A Comprehensive Review - Sahil P. Patel; Srushti J. Bhoraniya; Shruti D. Kalola; Atul Rukadikar; Renju Ravi; Samreen Farooqui; Charushila Rukadikar (Journal of Pharmacy and Bioallied Sciences)
The intricate community of bacteria that live in the gastrointestinal system, known as the gut microbiota, is essential to preserving human health and equilibrium. The pathophysiology of several chronic illnesses, including as neurological, cardiovascular, immunological, and metabolic disorders, has been progressively associated with its dysbiosis. This thorough analysis looks at the complex relationships that exist between gut microbiota and host physiology, examining processes including metabolic signaling, immunological regulation, and gut-brain axis communication. We discuss current developments in the study of the microbiome, with an emphasis on the role that the variety and makeup of gut microbes play in the development of chronic diseases. In order to restore microbial balance and lessen the severity of the condition, the study also covers new treatment approaches such as dietary changes, probiotics, prebiotics, and fecal microbiota transplantation. The development of novel, microbiome-based diagnostic and therapeutic strategies is made possible by an understanding of the complex link between the gut microbiota and chronic illnesses, highlighting the vital role that personalized medicine plays in enhancing health outcomes.